PENGARUH RASIO PROFITABILITAS DAN RASIO SOLVABILITAS TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2015 - Nurhasanah Anggraini; Bonifasius MH. Nainggolan (LPPM Universitas Asa Indonesia, 2017)
The purpose of the research is to analyzing the effect of profitability ratio (Return on Asset and Return on Equity) and leverage ratio (Debt to Asset Ratio dan Debt to Equity Ratio) on Stock Return on Manufacturing Companies from Indonesia Stock Exchange 2010 to 2015. The population consisted of manufacturing companies from Indonesia Stock Exchange 2010 to 2015 and a sample of 107 companies was obtained by using purposive sampling technique. Data analysis that will be used for this research are multi linier regression, classic assumption test (normality test, runs test, heterocedasticity test and multycolinearity test) whereas the hypothesis test including the F test, t test, partial correlation analysis and coefficient of determination (R2). From this analysis we can see the effect of Return on Asset, Return on Equity, Debt to Asset Ratio and Debt to Equity Ratio on Stock Return on Manufacturing Companies from Indonesia Stock Exchange 2010 to 2015.